Chapter 5: The evolution of welfare attitudes in Europe over the past four decades - Eick, Gianna Maria (Edward Elgar Publishing, 2023)
This chapter empirically investigates the evolution of public welfare attitudes over the past four decades from a birds-eye perspective. To do that, the Chapter reviews existing quantitative surveys on welfare attitudes. First, the Chapter finds that the public shows overall high and relatively stable levels of support for more government redistribution from 1981 to the present. During the post-crisis years after 2007/2008 (financial crisis), some (upward and downward) convergence trends across countries and time in attitudes were reinforced. Second, important socioeconomic cleavages are declining over time, too, particularly educational cleavages. Third, social investment policies, such as education, enjoy increasing levels of support, while the opposite trends can be seen for compensation policies, such as unemployment benefits. Overall, the Chapter finds emerging welfare solidarity across and within European countries and demonstrates that such attitudes increase in times of rising social risks and crises.